A Fitted Second Order Special Finite Difference Method for Singularly Perturbed Differential- Difference Equations Exhibiting Dual Layers (Journal of Informatics and Mathematical Sciences, 2020)
In this paper, a singularly perturbed differential-difference equation boundary value problem having boundary layer at both the end is examined. To solve such type of problems, a fitted special finite difference scheme is used. The differential-difference equation is replaced by an asymptotically equivalent singular perturbation problem using the Taylor's series expansion and afterwards fitted special finite difference scheme is applied. To demonstrate the applicability of this method, three numerical examples are solved and numerical results are presented which are in agreement with the available/exact results.
Keywords: Differential-difference equations; Boundary layer; Dual layer; Exponentially fitted finite difference methods